Analisis Efisiensi Pemasaran Komoditas Cabai Keriting Di Desa Touure Dua Kecamatan Tompaso Barat Kabupaten Minahasa - Lepa, Janet Evanglin Monita; Jocom, Sherly G.; Porajouw, Oktavianus (AGRI-SOSIOEKONOMI, 2023)
The purpose of this study was to analyze the marketing efficiency of curly chilies in Touure Dua Village, west Tompaso District, Minahasa Regency. This research eas carried out for 3 months starting from March to Mei 2022. The determination of the farmer sample was carried out using the purposive sampling method. The data used are primary data and secondary data. Primary data throught interviews and filling out questionnaires to 16 respondents, secondary data obtained from related agencies. The data analysis used was descriptive analysis method, namely the data collected in this study were tabularized, then grouped according to research variabels. The results showed that Touure Dua Village has 2 marketing channels, namely second-level marketing and third-level marketing, and it can be concluded that both marketing channels are all profitable. Marketing channel I is more efficient than marketing channel II. This is because marketing channel I is lower in marketing costs incurred and has a short channel, which means that curly chilies reach consumers faster and reduce the state of damage to curly chilies in the transportation and distribution process, then the higher the share received by farmers (farmer share) which is 74% and 71% for marketing channel I and marketing channel II, then the efficiency of marketing channel II can be said to be efficient because <50%, namely channel I marketing efficiency value is 1.11% while marketing channel II efficiency value is 2.06%. Based on the level of efficiency, channel I is more efficient because <50%. The efficiency process can change depending on the price of curly chili.